Reconciling resilience across ecological systems, species and subdisciplines - Capdevila, P; Stott, I; Oliveras Menor, I; Stouffer, DB; Raimundo, RLG; White, H; Barbour, M; Salguero-Gomez, R (Wiley, 2021)
Resilience has emerged as a key concept in ecology and conservation biology to understand and predict ecosystem responses to global change. In its broadest sense, resilience describes the ability of an ecosystem to resist, and recover from, a disturbance. However, the application of such a concept in different subdisciplines of ecology and in different study systems has resulted in a wide disparity of definitions and ways of quantifying resilience. This Special Feature, which spans the Journal of Ecology, Journal of Animal Ecology and Functional Ecology, provides an overview of how ecologists define, quantify, compare and predict resilience across different study systems. The 29 contributions to this Special Feature show the broad range of approaches used by ecologists to study resilience. Almost half of the contributions (48%) study resilience at the community level, with a 30% of them studying resilience at multiple levels of biological organisation. A large proportion of these articles are observational (42%), experimental (14%) or a combination of both (17%) while a 17% utilise theoretical or computational approaches. Although 38%, 21% and 14% of the studies were based solely on plants, animals or micro-organisms, respectively, 17% of them incorporated these multiple trophic levels. Synthesis. A unified ecological understanding of resilience across systems and taxa requires a trans-disciplinary consensus on what resilience actually is and how to best measure it. Here, we provide an overview of how ecologists define, quantify, compare and predict resilience across different ecological systems and subdisciplines, with reference to the diverse approaches used by contributions to this Special Feature. We identify four key recommendations to harmonise future efforts in resilience research: (a) define resilience using existing theoretical frameworks; (b) use common and comparable metrics to measure resilience; (c) clearly contextualise and define the pre- and post-disturbance state of the ecological system and (d) consider explicitly the disturbance type and regime impacting the system.